1996
DOI: 10.1161/01.res.78.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Reversibly Inhibits the Migration of Cultured Vascular Smooth Muscle Cells

Abstract: Augmentation of nitric oxide (NO) production in vivo decreases lesions in a variety of models of arterial injury, and inhibition of NO synthase exacerbates experimental intimal lesions. Both vascular smooth muscle cell (VSMC) proliferation and migration contribute to lesion formation. Although NO inhibits VSMC proliferation, its effects on VSMC migration are unknown. To test the hypothesis that NO inhibits VSMC migration independent of inhibition of proliferation, we examined migration of rat aortic VSMCs afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
226
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(235 citation statements)
references
References 22 publications
6
226
0
3
Order By: Relevance
“…NO has been shown to have opposing and complex effects on chemotactic responses exerted by various stimuli. For example, it has been shown that NO enhances chemotactic responses in some cell types (45,46,(61)(62)(63) upon certain stimuli, while inhibiting cell migration in others (47,64). Furthermore, NO has been shown to modulate T cell chemotaxis in Peyer's patches and in the nonlymphoid region of the intestine (65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO has been shown to have opposing and complex effects on chemotactic responses exerted by various stimuli. For example, it has been shown that NO enhances chemotactic responses in some cell types (45,46,(61)(62)(63) upon certain stimuli, while inhibiting cell migration in others (47,64). Furthermore, NO has been shown to modulate T cell chemotaxis in Peyer's patches and in the nonlymphoid region of the intestine (65).…”
Section: Discussionmentioning
confidence: 99%
“…Although NO can regulate migration in several cell types (45)(46)(47)(48), its role in chemokine-mediated chemotaxis in T cells is not known. We now report that SDF1␣ treatment activates NOS in Jurkat T cells.…”
mentioning
confidence: 99%
“…26 In addition, a possible direct antifibrogenic effect of NO donors is suggested by in vitro studies showing antiproliferative and antichemotactic actions of these compounds in vascular smooth muscle cells and glomerular mesangial cells. [27][28][29][30] However, the possible cellular and molecular mechanisms responsible for the action of NO donors in this setting have not been clarified.…”
Section: E Xperimental and Clinical Studies Have Indicated Thatmentioning
confidence: 99%
“…This raises the question regarding the precise nature of the Gab1/VAV interaction in proliferation and migration. When VSMCs are dedifferentiated, NO is capable of reducing motility [38] and blocking the increased motility in response to PDGF treatment. However, after an extended period of culture in dedifferentiated cells with insulin, a Gab1/SHP2 interaction may lead to a decrease in Rho A abundance en route to the increased motility [39] .…”
Section: Shp2 and Rhomentioning
confidence: 99%